The effect of L-carnitine in Tris egg yolk-based diluent on the quality of Pasundan bull semen preserved in chilled condition - Darussalam, I.; Arifiantini, R. I.; Supriatna, I.; Rasad, R. S. D. (Diponegoro University, 2020)
The study was conducted to investigatethe effect of L-Carnitine supplementation in Tris-eggyolk (TEY) diluents to optimize the quality of Pasundan bull liquid semen. Semen samples were collected from three Pasundan bulls (6 – 7 years old)usinganartificial vagina. Semen samples were evaluated macroscopically and microscopically, semen having ≥70% progressive motility, ≥500×106ml-1 sperm concentration and ≤ 20% sperm abnormalities were divided into 5 equal part. Each part wasdiluted with TEYand supplemented with0 mM(control), 1 mM, 2 mM, 3 mM and 4 mM L-Carnitine. Liquidsemen was storedat5°C.Sperm motility was evaluated every 12 h objectively using Computer Asissted Sperm Analysis (CASA) until progressive motilityreached 40%. The best diluent was demonstratedby progressive motility (PM)by TEY supplemented with 1 mM L-Carnitine(43.08±0.49%) that remained up to 108 h compared tothecontrol group (43.63±0.70%) that remained up to 72 h (P<0.05). In conclusion, 1 mM L-Carnitine in TEY was the best concentration for preservation of Pasundan bull semen stored in the liquid form.